2013
DOI: 10.1128/jb.00592-13
|View full text |Cite
|
Sign up to set email alerts
|

ppGpp-Dependent Negative Control of DNA Replication of Shiga Toxin-Converting Bacteriophages in Escherichia coli

Abstract: bThe pathogenicity of enterohemorrhagic Escherichia coli (EHEC) strains depends on the production of Shiga toxins that are encoded on lambdoid prophages. Effective production of these toxins requires prophage induction and subsequent phage replication. Previous reports indicated that lytic development of Shiga toxin-converting bacteriophages is inhibited in amino acidstarved bacteria. However, those studies demonstrated that inhibition of both phage-derived plasmid replication and production of progeny virions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 40 publications
2
31
0
Order By: Relevance
“…Prophage induction experiments were performed as described previously (Nowicki et al, 2013). Phage lytic development was provoked in lysogenic bacteria, growing at 37 uC in LB medium at A 600 0.2, by addition of 1 mg mitomycin C ml 21 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prophage induction experiments were performed as described previously (Nowicki et al, 2013). Phage lytic development was provoked in lysogenic bacteria, growing at 37 uC in LB medium at A 600 0.2, by addition of 1 mg mitomycin C ml 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Lytic development of lambdoid phages was studied in one step growth experiments in phage-infected bacteria, as described previously (Nowicki et al, 2013). Briefly, bacteria were grown in LB medium supplemented with MgSO 4 and CaCl 2 (to a final concentration of 10 mM each) at 37 uC to A 600 0.2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, there are studies aimed at detecting conditions that repress phage induction. Nejman et al (2011) have shown that plasmids derived from stx phages are not able to replicate in amino acid-starved bacteria, and Nowicki et al (2013) have studied the mechanism responsible for the inhibition of stx phage replication under amino acid starvation, identifying the role of the ppGpp alarmone. Nejman-Faleń czyk et al (2012) have suggested that reducing food consumption during illness, or even fasting, and providing minerals and citrate could be an option to manage STEC infections as they found that these conditions can delay and diminish the efficiency of phage particle formation.…”
Section: Human Stec Infections and Stx Phagesmentioning
confidence: 99%